Enhancing the Follow-up Assessment of Very Preterm Children with Regard to 5-Year IQ Considering Socioeconomic Status - Hoberg, Kathrin; Häusler, Martin; Orlikowsky, Thorsten; Lidzba, Karen (Zeitschrift für Geburtshilfe und Neonatologie, 2022)
Background Specifying peri- and postnatal factors in children born very preterm (VPT) that affect later outcome helps to improve long-term treatment.Aim To enhance the predictability of 5-year cognitive outcome by perinatal, 2-year developmental and socio-economic data. Subjects and outcome measures: 92 VPT infants, born 2007–2009, gestational age<32 weeks and/or birthweight of 1500 g, were assessed longitudinally including basic neonatal, socio-economic (SES), 2-year Mental Developmental Index (MDI, Bayley Scales II), 5-year Mental Processing Composite (MPC, Kaufman-Assessment Battery for Children), and Language Screening for Preschoolers data. 5-year infants born VPT were compared to 34 term controls.Results The IQ of 5-year infants born VPT was 10 points lower than that of term controls and influenced independently by preterm birth and SES. MDI, SES, birth weight and birth complications explained 48% of the variance of the MPC. The MDI proved highly predictive (r=0.6, R2=36%) for MPC but tended to underestimate the cognitive outcome. A total of 61% of the 2-year infants born VPT were already correctly classified (specificity of .93, sensitivity of .54). CHAID decision tree technique identified SES as decisive for the outcome for infants born VPT with medium MDI results (76–91): They benefit from effects associated to a higher SES, while those with a poor MDI outcome and a birth weight≤890 g do not.Conclusion Developmental follow-up of preterm children enhances the quality of prognosis and later outcome when differentially considering perinatal risks and SES.
Keywords: very preterm; socioeconomic status; birthweight; prediction; cognitive